Edukasi Budidaya Hidroponik Kepada Siswa SMK Diponegoro Kabupaten Pekalongan Sebagai Solusi Mengatasi Keterbatasan Lahan - Afiatan, Arbina Satria; Al Ramadhani, Farchan Mushaf; Mufid, Ahsarul; Handriatni, Ari; Badrudin, Ubad; Jazilah, Syakiroh; Alfarisy, Fariz Kustiawan; Wagiyana, Wagiyana; Cahyanita, Elvin; Ali Mudhor, Muhammad; Zahrah, Ninda Alza Nur (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to increase students' knowledge and interest in hydroponic cultivation as a solution to overcome land limitations. The community service activity was carried out at Diponegoro Vocational School. The implementation method consists of four stages: investigation, preparation, action, and reflection with educational materials, practice, and evaluation through pre-tests and post-tests. The results of the activity showed a significant increase in aspects of basic hydroponic knowledge, types of hydroponic systems, and hydroponic market opportunities, as indicated by changes in the percentage of students who understood the material before and after the activity. In addition, the level of student interest in hydroponic cultivation increased from 35.5% to 100% after participating in educational and practical activities. These findings prove that a practice-based learning approach can strengthen modern agricultural literacy and foster entrepreneurial motivation.